351 Dear Program Director: Evaluating Implicit Bias in Neurosurgery Residency Letters of Recommendation. (1st April 2022) - Graves, Erin; Coyle, Anne; Erkmen, Cherie; Erkmen, Kadir
Abstract : INTRODUCTION: Despite comprising half of medical students, women represent 25% of neurosurgery applicants, 17% of residents and 12% of practicing neurosurgeons. This trend suggests "leaks" in the career pipeline for female neurosurgeons. The NRMP Program Director Survey has shown that neurosurgery programs identify Step 1 score and letters of recommendation (LORs) as the most important factors in selecting applicants to interview. Other specialties have evaluated implicit biases in LORs, but no such study exists in neurosurgery. METHODS: Retrospective analysis of LORs for neurosurgery applicants interviewed between 2014-2020. LORs were evaluated using the Linguistic Inquiry & Word Count (LIWC) software and a Reader Scoring System. The LIWC dictionary and a custom dictionary containing additional categories (e.g. grindstone) and terms (e.g. hardworking) were used. Analyses were done using SAS. RESULTS: 218 applications were reviewed (81.1% male, n=177), for a total of 827 letters. LIWC analysis showed significant differences in word count (331 females vs. 296 males, p = 0.017), ability words (6.61 females vs. 5.51 males, p = 0.018), and agentic words (6.31 females vs. 5.53 males, p = 0.020). Female letters showed a higher average number of grindstone, communal and commitment words. The Reader Scoring System showed similarities between candidates, but revealed a trend that in female letters writers mention personal attributes and "career" versus "residency" potential. CONCLUSION: This is the first study to evaluate for implicit gender bias within neurosurgery LORs. LORs are key in the selection process and therefore represent one area to target when it comes to increasing female representation in neurosurgery. Our study showed that female applicant's letters were longer, had more ability and agentic terms, and trended towards more grindstone, communal and commitment words.